2011
DOI: 10.1136/pgmj.2010.105569
|View full text |Cite
|
Sign up to set email alerts
|

Using the ISBAR handover tool in junior medical officer handover: a study in an Australian tertiary hospital

Abstract: Background Despite being essential to patient care, current clinical handover practices are inconsistent and error prone. Efforts to improve handover have attracted attention recently, with the ISBAR tool increasingly utilised as a format for structured handover communication. However, ISBAR has not been validated in a junior medical officer setting. Objective To assess the effect of the ISBAR handover tool on junior medical officer (JMO) handover communication in an Australian hospital. Methods JMOs who parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 18 publications
1
69
0
2
Order By: Relevance
“…(17) Even in standard face-to-face handover systems, communication challenges can still occur if the transfer of care is not smoothly executed. (3,8,18,19) Many studies that evaluated handover processes reported that interruptions, environmental factors (e.g. noise, crowding) and specifi c patient care requirements for both groups of staff involved in the handover resulted in an unstructured and error-prone handover process; (9,15,20) this is similar to the fi ndings of the present study.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…(17) Even in standard face-to-face handover systems, communication challenges can still occur if the transfer of care is not smoothly executed. (3,8,18,19) Many studies that evaluated handover processes reported that interruptions, environmental factors (e.g. noise, crowding) and specifi c patient care requirements for both groups of staff involved in the handover resulted in an unstructured and error-prone handover process; (9,15,20) this is similar to the fi ndings of the present study.…”
Section: Discussionsupporting
confidence: 85%
“…This scenario could be due to senior PIs' preference for conveying patient information at a face-to-face handover instead of via written communication, and points to the need for a communication form that guarantees compliance even among senior staff. (8,21) Communication improved not only as a result of changes in the content of the SBAR handover document, but also in the use of the document during face-to-face handover to relay its content ('timeout'); the latter was a requirement of the new PETS handover protocol. Therefore, our results differed from Joffe et al's, (22) as our recipients appreciated the use of the SBAR handover document as a format for face-to-face verbal handover and as a reference for other CICU caregivers who did not participate in the actual handover.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Other recommendations to improve the ToC process include training sessions, senior supervision, and the use of electronic aids. 34 The following 5 principles reflect effective ToCs 23 :…”
Section: Identified Strategies For Tocsmentioning
confidence: 99%